Mapa de potencial arqueológico de la Estancia Fortín Chacabuco (PNNH-APN): primeros resultados integrando información arqueológica, histórica, geomorfológica y ambiental - Bianchi Villelli, Marcia Eliana (2021)
This work presents the first results of an interdisciplinary project about the archaeological potentiality of the Fortín Chacabuco ranch, as the first instance in order to build an archaeological baseline in the Nahuel Huapi National Park (Nationals Parks Administration). The integration of geoenvironmental, archaeological and historical information was used as a starting point to elaborate a map and rank the space in terms of potential for human use. The initial results allowed to survey at least five archaeological sites and other relevant features that indicate that human occupation of this sector of the National Park was spatially and temporally heterogeneous. These results also constitute the first record to formulate an archaeological heritage management plan in collaboration with the Estancia Fortín Chacabuco administration and the Nahuel Huapi National Park and Nationals Parks Administration professionals.